2022
DOI: 10.1039/d1mh01568k
|View full text |Cite|
|
Sign up to set email alerts
|

Progressive p-channel vertical transistors fabricated using electrodeposited copper oxide designed with grain boundary tunability

Abstract: We suggested strategically designed electrodeposition method for the coating of p-type copper(I) oxide (Cu2O) channel for oxide thin film transistors. Up to now, conventional p-type oxide semiconductors have revealed poor...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Because this device requires the secure performances of the spacer-free V-Tr as a basic platform, we fabricated a p-type-driven V-Tr exhibiting superior electrical performances and the following figures of merit: V th = 1.1 V, μ FE = 8 cm 2 V −1 s −1 , SS = 0.26 V dec −1 , and on/off current ratio = 5 × 10 6 , which were comparable to those of conventional planar amorphous InGaZnO (a-IGZO) TFTs despite the use of the electrodeposited Cu 2 O channels. 49 However, the transistor still does not operate by the minority carriers in the low-off-current forward bias region, indicating the absence of strong minority-carrier-induced inversion. Because the minority-carrier concentration is much lower than majority-carrier one, although the strong surface-potential-induced compensation effect in the channel layer intrinsically prohibits the role of the minority carriers, the Cu 2 O exhibits the appropriate band alignment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because this device requires the secure performances of the spacer-free V-Tr as a basic platform, we fabricated a p-type-driven V-Tr exhibiting superior electrical performances and the following figures of merit: V th = 1.1 V, μ FE = 8 cm 2 V −1 s −1 , SS = 0.26 V dec −1 , and on/off current ratio = 5 × 10 6 , which were comparable to those of conventional planar amorphous InGaZnO (a-IGZO) TFTs despite the use of the electrodeposited Cu 2 O channels. 49 However, the transistor still does not operate by the minority carriers in the low-off-current forward bias region, indicating the absence of strong minority-carrier-induced inversion. Because the minority-carrier concentration is much lower than majority-carrier one, although the strong surface-potential-induced compensation effect in the channel layer intrinsically prohibits the role of the minority carriers, the Cu 2 O exhibits the appropriate band alignment.…”
Section: Resultsmentioning
confidence: 99%
“…Unlike the planar ambipolar transistors fabricated using bilayered individual p- and n-type stacking channels, which exhibit considerable off-currents, our V-Trs exhibit optimally reduced currents in the depleted-carrier positive bias region, which is essential for low-power-consumption operation. 49 To demonstrate the field-induced n-type channel behavior in this channel, although a minority-carrier-driven operation must exhibit strong inversion, which is typical of Si-based MOSFETs, this is conceptually difficult in simple Cu 2 O transistors. Nevertheless, p-type Cu 2 O exhibits an adequate conduction band position and relatively narrow bandgap for driving strong inversion [Scheme 2(a)].…”
Section: Resultsmentioning
confidence: 99%
“…Field-effect passivation caused by the high negative fixed charge of the Al 2 O 3 interfacial layer significantly improved the TFT’s performance by reducing the density of deep trap states and electron accumulation in the semiconductor layer in the device’s off-state. In 2022, Jung et al first reported the study of an electrodeposited method to design troublesome p-Type oxide Cu 2 O for novel vertical transistors [ 98 ]. In their study, the Cu 2 O vertical FET exhibited good performance and qualified electrical and long-term stability characteristics under various environments.…”
Section: P-type Cu 2 O Tftsmentioning
confidence: 99%